MAKNA KANYOUKU YANG MENGANDUNG UNSUR 手 (TE) ‘TANGAN’ DALAM BAHASA JEPANG: KAJIAN SEMANTIK KOGNITIF - Alwirienaldy Alwirienaldy; Arza Aibonotika; Yenny Aristia Nst (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research focuses on the cognitive semantic study of the meaning of kanyouku in the Japanese language that contains the element 手 (te), which means 'hand'. Kanyouku refers to compound words in Japanese where two or more kanji characters are combined to create a new meaning. The specific focus of this study is on kanyouku that includes the kanji character 手 (te), which is associated with the concept of 'hand' in Japanese culture. The objective of this study is to explore the cognitive processes involved in understanding the meaning of kanyouku that contains the element 手 (te). Through a comprehensive analysis of the semantic and cognitive aspects, this research aims to uncover the underlying conceptual structures and associations related to the use of 手 (te) in kanyouku. Overall, this research aims to enhance our understanding of the cognitive and semantic aspects of kanyouku that contain the element 手 (te) in the Japanese language. By investigating the underlying conceptual structures and cognitive processes, this study will provide valuable insights into the rich and nuanced meaning of 手 (te) and its implications in Japanese language and culture.Key words: Idiom, Kanyouku, Cognitive Semantic, Te ‘hand’, Cognitive.